2015
DOI: 10.1176/appi.neuropsych.13070153
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antineuronal Antibodies in Tunisian Psychiatric Inpatients

Abstract: The authors aimed to determine the prevalence of antineuronal antibodies in 103 psychiatric inpatients and 41 control subjects with no history of malignancies or neurological disorders. All sera were tested by indirect immunofluorescence and positive sera by immunoblot. Using immunofluorescence, antineuronal nuclear autoantibodies were detected in 20 patients and none of the control subjects, and antibodies reacted with the cytoplasm of Purkinje cells in six patients and two control subjects. The immunoblot co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…disord.47/170338/13788/3100/42?? ; 4024Amph, Ma1, Ma2, CRMP-5/CV2, Tr, Hu, Rec, Ri, YoIIFDSM-IV100%/100%-Moon et al 2014 [47]South Korea– 12-14S (r)Non-stiff amphiphysin syndrome20/207/2058*; 4012Amph., Hu, Yo, Ri, Ma2, CRMP-5.Im.bl.None25%/25%Irritability, psychosisLaadhar et al 2015 [17]Tunisia -?S (c)Psychiatric patHealthy controls5/1030/410/1030/4143*; 2841*; 22ANNA, PCA1, ANAHu, Ri, YoWB, IIFDSM-IV100%/100%Schizophrenia, schizoaff. And bipolar disord.Haukanes et al 2015 [43]Norway -?S (c)ADHD patHealthy controls0/1690/560/1690/5633*; 5035*; 55Yo, Amph, CRMP-5, Ma2, Ri, HuYo, Amph, CRMP-5/CV2, Ma2, Ri, HuIm.bl, WB, IIFDSM-IV100%/−-Kruse et al 2015 [44]US (Roch)- 02–11S (r)Psychiatric inpatHealthy controls1/2130/173??…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…disord.47/170338/13788/3100/42?? ; 4024Amph, Ma1, Ma2, CRMP-5/CV2, Tr, Hu, Rec, Ri, YoIIFDSM-IV100%/100%-Moon et al 2014 [47]South Korea– 12-14S (r)Non-stiff amphiphysin syndrome20/207/2058*; 4012Amph., Hu, Yo, Ri, Ma2, CRMP-5.Im.bl.None25%/25%Irritability, psychosisLaadhar et al 2015 [17]Tunisia -?S (c)Psychiatric patHealthy controls5/1030/410/1030/4143*; 2841*; 22ANNA, PCA1, ANAHu, Ri, YoWB, IIFDSM-IV100%/100%Schizophrenia, schizoaff. And bipolar disord.Haukanes et al 2015 [43]Norway -?S (c)ADHD patHealthy controls0/1690/560/1690/5633*; 5035*; 55Yo, Amph, CRMP-5, Ma2, Ri, HuYo, Amph, CRMP-5/CV2, Ma2, Ri, HuIm.bl, WB, IIFDSM-IV100%/−-Kruse et al 2015 [44]US (Roch)- 02–11S (r)Psychiatric inpatHealthy controls1/2130/173??…”
Section: Resultsmentioning
confidence: 99%
“…We identified 27 original publications that met eligibility criteria [2, 17, 2549]. Data about the serum prevalence of well-characterized onconeural antibodies in patients with psychiatric disorders were available from 6 papers [17, 29, 41, 43, 44, 46]. Authors of 1 paper reported on the prevalence of anti-Purkinje cell antibodies “similar to those found in paraneoplastic cerebellar degeneration”, but did not specify if tests for well-characterized onconeural antibodies were performed [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have recently called for prevalence studies on antibodies targeting intracellular onconeural antigens in psychiatric patients, 10,11 suggesting that these antibodies could contribute to the pathophysiology of some psychotic disorders. Our findings do not support this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have recently called for studies addressing the role of onconeural antibodies targeting intracellular antigens in psychiatric patients. 10,11 To investigate this issue further, we examined the prevalence of onconeural antibodies in a large sample of patients admitted to an acute psychiatric center.…”
mentioning
confidence: 99%